Demographic Patterns and Transitions in 18-20th Century Hungary. County Pest-Pilis-Solt-Kiskun in the Late 18th and Early 20th Centuries - Pet́er Ori (Hungarian Demographic Research Institute, 2007)
This paper aims at analysing the different kinds of demographic behaviour and the local variations of demographic development in Hungary in the late 18th and 19th centuries. The analysis is a part of a larger country-wide research based on samples which reconstructs the country's demographic development in the mentioned period. In the analysis the data of about 200 settlements of the county of Pest-Pilis-Solt (around the capital) are used. The territory of the county was very varied in terms of ethnicity (Hungarians, Germans, Slovaks, Serbs, Croats, Jews), religion (Roman Catholics, Calvinists, Lutherans, Orthodox), geographic conditions and farming. Thus the county itself can be regarded as a representative sample of the country. The data used in the analysis are those of some 18th century population censuses (Conscriptio Animarum, 1774-1783 and the census of Joseph II, 1784-1787), some 19th century censuses (1869, 1880, 1890 and 1900) and local population movement registers (1828-1949). On the basis of the settlement level variables the different demographic patterns of the county are going to be separated by cluster-analysis with special respect to the differences in fertility at the end of the 19th century. Some variables relating to ethnicity, religion, occupational distribution, and farming can help to interpret the demographic differences pointed out by the former statistical analysis. Differences in fertility can be mainly analysed only for the period of the early 20th century, during the transition from the "traditional" to the "modern" demographic system. The analysis can be the basis of further research using samples and can show the demographic diversity of a region generally regarded as a transitional type between 'western' and 'eastern' demographic systems helping to explain the content of those transitional characteristics.
Keywords: 300; Einwanderung; Migranten; Ethnische Gruppe; Sozialkapital; Ungarn